Everyday choices : the role of competing authorities and social institutions in politics and development - Lust, Ellen (New York : Cambridge University Press, 2022)
"Scholars and practitioners seek development solutions through the engineering and strengthening of state institutions. Yet, the state is not the only or the primary arena shaping how citizens, service providers and state officials engage in actions that constitute politics and development. These individuals are members of religious orders, ethnic communities, and other groups that make claims on them, creating incentives that shape their actions. Recognizing how individuals experience these claims and view the choices before them is essential to understanding political processes and development outcomes. This Element establishes a framework elucidating these forces, which is key to knowledge accumulation, designing future research and effective programming. Taking an institutional approach, this Element explains how the salience of arenas of authority associated with various communities and the nature of social institutions within them affect politics and development. This title is also available as Open Access on Cambridge Core"--
State centrality in politics and development -- Conceptualizing arenas of authority and social institutions -- Which arenas matter, when and why -- Social institutions, politics and development outcomes -- Reconsidering "state" institutions.
Keywords: Social institutions -- Political aspects; Authority -- Political aspects; Community development -- Political aspects